2013
DOI: 10.1007/s12088-013-0394-z
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Protective Efficacy of Clostridium butyricum Against Fish Pathogen Infections

Abstract: Most pathogens in intestine are opportunist, called "opportunistic pathogens" that usually do not cause disease in a healthy host. Only when the host's resistance is lowered or the intestinal microecological balance is destroyed, the opportunistic pathogens are capable of causing disease. Here, two opportunistic pathogens, Salmonella enteritidis and Vibrio parahaemolyticus were chosen to test the possible antagonistic effect of the probiotic agent Clostridium butyricum on these pathogens infections in vitro us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…CB can also produce prebiotics, including bacteriocin, lipoteichoic acid, and hydrogen, all of which serve to regulate animal antioxidation and antibacterial functions ( Pan, 2006 ; Gao et al, 2011 ; Junghare et al, 2012 ). It was reported that CB and its lipoteichoic acid components could inhibit the growth of pathogens, including E. coli , Salmonella enteritidis , and Vibrio parahaemolyticus ( Gao et al, 2011 , 2013 ). In vertebrates, CB could improve the growth, antioxidation, and immune function of broilers ( Liao et al, 2015a , b ; Zhang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…CB can also produce prebiotics, including bacteriocin, lipoteichoic acid, and hydrogen, all of which serve to regulate animal antioxidation and antibacterial functions ( Pan, 2006 ; Gao et al, 2011 ; Junghare et al, 2012 ). It was reported that CB and its lipoteichoic acid components could inhibit the growth of pathogens, including E. coli , Salmonella enteritidis , and Vibrio parahaemolyticus ( Gao et al, 2011 , 2013 ). In vertebrates, CB could improve the growth, antioxidation, and immune function of broilers ( Liao et al, 2015a , b ; Zhang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clostridium butyricum found in soil and intestines of healthy animals and humans is a butyricum acid‐producing, spore‐forming, Gram‐positive and obligate anaerobic rod bacterium, which can produce endospores and be able to survive in media of low pH and relatively high bile concentration (Zhang et al., ). Moreover, C. butyricum can prevent disturbances of intestinal microflora (Gao et al., ; Song, Wu, Cai, Zhang & Zheng, ), accrete with available intestinal bacteria and modulate intestinal microbial balance, which is supposed to be a potential probiotic in animal feed (Pan, Wu, Zhang et al., ; Yang et al., ). C. butyricum has been mainly studied in human (Ito et al., ; Seki et al., ) and terrestrial animals (Kong, He, Jia, Zhu & Ruan, ; Liao et al., ; Yang et al., ; Zhang et al., ; Zhuang, Jiang, Jia & Yan, ), but rarely in aquatic organisms (Pan, Wu, Song, Tang & Zhao, ; Song et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…butyricum can prevent disturbances of intestinal microflora (Gao et al, 2013;Song, Wu, Cai, Zhang & Zheng, 2006), accrete with available intestinal bacteria and modulate intestinal microbial balance, which is supposed to be a potential probiotic in animal feed (Pan, Wu, Zhang et al, 2008;Yang et al, 2012). C. butyricum has been mainly studied in human (Ito et al, 1997;Seki et al, 2003) and terrestrial animals (Kong, He, Jia, Zhu & Ruan, 2011;Liao et al, 2015;Yang et al, 2012;Zhuang, Jiang, Jia & Yan, 2015), but rarely in aquatic organisms Song et al, 2006).…”
mentioning
confidence: 99%
“…2008) and the production of organic acids during the process of fermentation (Gao et al . 2013). In addition, C. butyricum can stimulate the activities of antioxidant enzymes (serum superoxide dismutase (SOD), phenoloxidase, acid phosphatases and lysozyme) and level of immunoglobulin M (IgM) (Song et al .…”
Section: Mechanisms Of Actionmentioning
confidence: 99%